Prenatal care in the Brazilian public health services - Maria do Carmo Leal; Ana Paula Esteves-Pereira; Elaine Fernandes Viellas; Rosa Maria Soares Madeira Domingues; Silvana Granado Nogueira da Gama (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To verify regional inequalities regarding access and quality of prenatal and birth care in Brazilian public health services and associated perinatal outcomes METHODS Birth in Brazil was a national hospital-based survey conducted between 2011 and 2012, which included 19,117 women with public-funded births. Regional differences in socio-demographic and obstetric characteristics, as well as differences in access and quality of prenatal and birth care were tested by the χ2 test. The following outcomes were assessed: spontaneous preterm birth, provider-initiated preterm birth, low birth weight, intrauterine growth restriction, Apgar in the 5th min < 8, neonatal and maternal near miss. Multiple and non-conditional logistic regressions were used for the analysis of the associated perinatal outcomes, with the results expressed in adjusted odds ratio and 95% confidence interval. RESULTS Regional inequalities regarding access and quality of prenatal and birth care among users of public services are still evident in Brazil. Pilgrimage for birth associated with all perinatal outcomes studied, except for intrauterine growth restriction. The odds ratios ranged between 1.48 (95%CI 1.23-1.78) for neonatal near miss and 1.62 (95%CI 1.27-2.06) for provider-initiated preterm birth. Among women with clinical or obstetric complications, pilgrimage for birth associated with provider-initiated preterm birth and with Apgar in the 5th min < 8, odds ratio of 1.98 (95%CI 1.49-2.65) and 2.19 (95%CI 1.31-3.68), respectively. Inadequacy of prenatal care associated with spontaneous preterm birth in both groups of women, with or without clinical or obstetric complications. CONCLUSION Improvements in the quality of prenatal care, appropriate coordination and comprehensive care at the time of birth have a potential to reduce prematurity rates and, consequently, infant morbidity and mortality rates in the country.